The Influence of the Method of Supplying Fuel Components on the Characteristics of a Rotating Detonation Engine. Issue 3 (17th February 2021) - Frolov, S. M.; Smetanyuk, V. A.; Ivanov, V. S.; Basara, B.
ABSTRACT: The computational technology jointly developed by the N. N. Semenov Federal Research Center for Chemical Physics (ICP) and AVL LIST GmbH is used for simulating the operation process in a Rotating Detonation Engine (RDE) with an annular combustor and separate supply of fuel (natural gas (NG)) and oxidizer (gaseous oxygen). Particular attention is paid to turbulent and molecular mixing of fuel and oxidizer in the combustor and its effect on the RDE operation process. Two different schemes of fuel and oxidizer supply are considered at fixed values of their mass flow rates. In the first, the oxidizer is supplied axially through the annular slot, whereas the fuel is supplied radially through the belt of multiple distributed holes in the outer wall of the combustor. In the second, the oxidizer and fuel replace each other while their mass flow rates are kept fixed. Such a replacement is shown to lead to restructuring of the operation process: the mode with three equidistant detonation waves (DWs) rotating over the fire head of the RDE is replaced by the mode with a single rotating DW, which is the indication of approaching the marginal operation conditions. Moreover, such a replacement leads to a significant decrease in the combustion completeness of the fuel components and to the decrease in the average pressure in the RDE combustor.